Abrupt elastic-to-plastic transition in pentagonal nanowires under bending - Vlassov, Sergei; Mets, Magnus; Polyakov, Boris; Bian, Jianjun; Dorogin, Leonid; Zadin, Vahur (Beilstein Journal of Nanotechnology, 2019)
In this study, pentagonal Ag and Au nanowires (NWs) were bent in cantilever beam configuration inside a scanning electron microscope. We demonstrated an unusual, abrupt elastic-to-plastic transition, observed as a sudden change of the NW profile from smooth arc-shaped to angled knee-like during the bending in the narrow range of bending angles. In contrast to the behavior of NWs in the tensile and three-point bending tests, where extensive elastic deformation was followed by brittle fracture, in our case, after the abrupt plastic event, the NW was still far from fracture and enabled further bending without breaking. A possible explanation is that the five-fold twinned structure prevents propagation of critical defects, leading to dislocation pile up that may lead to sudden stress release, which is observed as an abrupt plastic event. Moreover, we found that if the NWs are coated with alumina, the abrupt plastic event is not observed and the NWs can withstand severe deformation in the elastic regime without fracture. The coating may possibly prevent formation of dislocations. Mechanical durability under high and inhomogeneous strain fields is an important aspect of exploiting Ag and Au NWs in applications like waveguiding or conductive networks in flexible polymer composite materials.
Keywords: finite element method; mechanical properties; molecular dynamics; nanowires

(untitled) - Elechiguerra, J. L.; Reyes-Gasga, J.; Yacaman, M. J. (J. Mater. Chem., 2006)

(untitled) - Sun, Y.; Xia, Y. (Adv. Mater. (Weinheim, Ger.), 2002)

(untitled) - Reyes-Gasga, J.; Elechiguerra, J. L.; Liu, C.; Camacho-Bragado, A.; Montejano-Carrizales, J. M.; Jose Yacaman, M. (J. Cryst. Growth, 2006)

(untitled) - Chen, H.; Gao, Y.; Zhang, H.; Liu, L.; Yu, H.; Tian, H.; Xie, S.; Li, J. (J. Phys. Chem. B, 2004)

(untitled) - Gryaznov, V. G.; Heydenreich, J.; Kaprelov, A. M.; Nepijko, S. A.; Romanov, A. E.; Urban, J. (Cryst. Res. Technol., 1999)

(untitled) - Dorogin, L. M.; Vlassov, S.; Kolesnikova, A. L.; Kink, I.; Lõhmus, R.; Romanov, A. E. (Phys. Status Solidi B, 2010)

(untitled) - Wu, J. Y.; Nagao, S.; He, J. Y.; Zhang, Z. L. (Nano Lett., 2011)

(untitled) - Loh, O. Y.; Espinosa, H. D. (Nat. Nanotechnol., 2012)

(untitled) - Li, M.; Bhiladvala, R. B.; Morrow, T. J.; Sioss, J. A.; Lew, K.-K.; Redwing, J. M.; Keating, C. D.; Mayer, T. S. (Nat. Nanotechnol., 2008)

(untitled) - Zhang, R.; Engholm, M. (Nanomaterials, 2018)

(untitled) - Shi, Y.; He, L.; Deng, Q.; Liu, Q.; Li, L.; Wang, W.; Xin, Z.; Liu, R. (Micromachines, 2019)

(untitled) - Xu, F.; Zhu, Y. (Adv. Mater. (Weinheim, Ger.), 2012)

(untitled) - Amjadi, M.; Pichitpajongkit, A.; Lee, S.; Ryu, S.; Park, I. (ACS Nano, 2014)

(untitled) - Huang, G.-W.; Xiao, H.-M.; Fu, S.-Y. (Sci. Rep., 2015)

(untitled) - Lee, C.-J.; Park, K. H.; Han, C. J.; Oh, M. S.; You, B.; Kim, Y.-S.; Kim, J.-W. (Sci. Rep., 2017)

(untitled) - Helgason, R.; Banavali, A.; Lai, Y. (Med. Devices Sens., 2019)

(untitled) - Lee, J.-Y.; Connor, S. T.; Cui, Y.; Peumans, P. (Nano Lett., 2008)

(untitled) - West, P. R.; Ishii, S.; Naik, G. V.; Emani, N. K.; Shalaev, V. M.; Boltasseva, A. (Laser Photonics Rev., 2010)

(untitled) - Wang, W.; Yang, Q.; Fan, F.; Xu, H.; Wang, Z. L. (Nano Lett., 2011)

(untitled) - Wang, Y.; Guo, X.; Tong, L.; Lou, J. (J. Lightwave Technol., 2014)

(untitled) - Wei, H.; Xu, H. (Nanophotonics, 2012)

(untitled) - Kartopu, G.; Choy, K.-L.; Yalçın, O. (Phys. Scr., 2014)

(untitled) - Nauert, S.; Paul, A.; Zhen, Y.-R.; Solis, D., Jr; Vigderman, L.; Chang, W.-S.; Zubarev, E. R.; Nordlander, P.; Link, S. (ACS Nano, 2014)

(untitled) - Niekiel, F.; Spiecker, E.; Bitzek, E. (J. Mech. Phys. Solids, 2015)

(untitled) - Zhu, Y.; Qin, Q.; Xu, F.; Fan, F.; Ding, Y.; Zhang, T.; Wiley, B. J.; Wang, Z. L. (Phys. Rev. B, 2012)

(untitled) - Jing, G. Y.; Duan, H. L.; Sun, X. M.; Zhang, Z. S.; Xu, J.; Li, Y. D.; Wang, J. X.; Yu, D. P. (Phys. Rev. B, 2006)

(untitled) - Wu, B.; Heidelberg, A.; Boland, J. J.; Sader, J. E.; Sun, X.; Li, Y. (Nano Lett., 2006)

(untitled) - Vlassov, S.; Polyakov, B.; Dorogin, L. M.; Antsov, M.; Mets, M.; Umalas, M.; Saar, R.; Lõhmus, R.; Kink, I. (Mater. Chem. Phys., 2014)

(untitled) - Mets, M.; Antsov, M.; Zadin, V.; Dorogin, L. M.; Aabloo, A.; Polyakov, B.; Lõhmus, R.; Vlassov, S. (Phys. Scr., 2016)

(untitled) - Lucas, M.; Leach, A. M.; McDowell, M. T.; Hunyadi, S. E.; Gall, K.; Murphy, C. J.; Riedo, E. (Phys. Rev. B, 2008)

(untitled) - Qin, Q.; Yin, S.; Cheng, G.; Li, X.; Chang, T.-H.; Richter, G.; Zhu, Y.; Gao, H. (Nat. Commun., 2015)

(untitled) - Kim, F.; Sohn, K.; Wu, J.; Huang, J. (J. Am. Chem. Soc., 2008)

(untitled) - Vlassov, S.; Polyakov, B.; Dorogin, L. M.; Vahtrus, M.; Mets, M.; Antsov, M.; Saar, R.; Romanov, A. E.; Lõhmus, A.; Lõhmus, R. (Nano Lett., 2014)

(untitled) - Vlassov, S.; Polyakov, B.; Vahtrus, M.; Mets, M.; Antsov, M.; Oras, S.; Tarre, A.; Arroval, T.; Lõhmus, R.; Aarik, J. (Nanotechnology, 2017)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Williams, P. L.; Mishin, Y.; Hamilton, J. C. (Modell. Simul. Mater. Sci. Eng., 2006)

(untitled) - Nosé, S. (J. Chem. Phys., 1984)

(untitled) - Hoover, W. G. (Phys. Rev. A, 1985)

(untitled) - Peng, P.; Liu, L.; Gerlich, A. P.; Hu, A.; Zhou, Y. N. (Part. Part. Syst. Charact., 2013)

(untitled) - Polyakov, B.; Dorogin, L. M.; Vlassov, S.; Antsov, M.; Kulis, P.; Kink, I.; Lohmus, R. (Eur. Phys. J. B, 2012)

(untitled) - Falvo, M. R.; Taylor, R. M., II; Helser, A.; Chi, V.; Brooks, F. P., Jr; Washburn, S.; Superfine, R. (Nature, 1999)

(untitled) - Narayanan, S.; Cheng, G.; Zeng, Z.; Zhu, Y.; Zhu, T. (Nano Lett., 2015)

(untitled) - Leach, A. M.; McDowell, M.; Gall, K. (Adv. Funct. Mater., 2007)